Motivational strategies in interventions for intimate partner violence offenders : a systematic review and meta-analysis of randomized controlled trials - Santirso, Faraj A. (Colegio Oficial de Psicólogos de Madrid, 2020)
Previous research suggests that the inclusion of motivational strategies in interventions for intimate partner violence (IPV) offenders could increase their effectiveness. This review evaluated the effectiveness of interventions for IPV offenders that includes motivational strategies to reduce physical and psychological IPV, treatment dropout, official recidivism to IPV offending, and to increase intervention attendance dose. The present systematic review and meta-analysis were conducted using PRISMA guidelines. The following databases were searched from 1983 to 2018 for randomized controlled trials (RCTs) of interventions for IPV offenders that incorporated motivational strategies for adult participants that included men and included IPV behaviors as outcomes: Cochrane Collaboration, MEDLINE, EMBASE, PsycINFO and CINAHL. A total 1,134 studies were identified, 12 RCTs were included in the narrative review and 7 in the meta-analysis. Results indicated that IPV interventions that incorporated motivational strategies were significantly more effective in increasing the intervention dose and reducing dropout than interventions without motivational strategies. IPV offenders receiving interventions with motivational strategies were 1.73 times less likely to intervention dropout compared to those in interventions without such strategies. For physical and psychological IPV and official recidivism (e.g., rearrests, police record), evidence favored interventions with motivational strategies, although not significantly. These findings have important practical implications, especially considering the high dropout rates in IPV offender programs and the link between dropout and higher rates of recidivism.